Implementação de Roteamento IPv4 em SDN com P4 - VITOR HUGO DOS SANTOS DUARTE (2023)
The Internet has a fundamental role in contemporary society, connecting devices and facilitating data transfer on a global scale. However, constant technological advancement challenges the structure and management of the networks that make up the Internet. Given the growing demand for speed, flexibility, and fficiency, exploring new approaches to incorporating innovative functionalities into networks is imperative. In this context, Software-Defined Networks (SDN) emerge as a possible solution by allowing the separation of the data and control plane and providing more effective network management. With the increase in the number of protocols in the data plane, the need for dynamic programming goes beyond the static model. Given this, the P4 programming language stands out, enabling protocol-independent programming in the data plane and allowing it to deal with the growing diversity of protocols. Within this evolution, routers are crucial for forwarding packets to their correct destinations. The main focus of this work is the development of an IP router based on SDN using the P4 data-plane programming language that meets the RFC1812 standard. The router validation is performed through emulation using Mininet.